Respuesta :

Answer:

The answer is below, just substitute the x values in the function and simplify

Step-by-step explanation:

 y = 2x               x            y = 2(x)                     y

                         -4             y = 2(-4)                  -8

                         -3            y = 2(-3)                   -6

                         -2             y = 2(-2)                  -4

                         -1             y = 2(-1)                    -2

                           0            y = 2(0)                     0

                           1             y = 2(1)                      2

                           2           y = 2(2)                      4

                           3            y = 2(3)                      6